Monitoring and reporting attacks on education in the Democratic Republic of the Congo and Somalia. Issue 2 (9th August 2017) - Bennouna, Cyril; van Boetzelaer, Elburg; Rojas, Lina; Richard, Kinyera; Karume, Gang; Nshombo, Marius; Roberts, Leslie; Boothby, Neil
Abstract : The United Nations' Monitoring and Reporting Mechanism is charged with documenting six grave violations against children in a time of conflict, including attacks on schools. Many of these incidents, however, remain unreported across the globe. This study explores whether or not a local knowledge base of education and child protection actors in North and South Kivu Provinces, Democratic Republic of the Congo, and in Mogadishu, Somalia, could contribute to a more complete record of attacks on education in those areas. Hundreds of semi‐structured interviews were conducted with key informants across the three settings, and in total 432 attacks on education were documented. Purposive samples of these reports were verified and a large majority was confirmed. Local non‐governmental organisations and education institutions were most knowledgeable about these incidents, but most never reported them to a monitoring authority. The study concludes that attack surveillance and response were largely insufficient, and recommends investing in mechanisms that utilise local knowledge to address these shortcomings.